THE IMPACT OF CLOUD COMPUTING ON FINANCIAL ACCOUNTING - EVALUATING THE IMPACT OF CLOUD COMPUTING ON ACCOUNTING FIRMS - M Shivarajappa (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The advent of cloud computing has transformed the way businesses operate, including financial accounting. This paper explores the impact of cloud computing on financial accounting, highlighting its benefits, challenges, and future directions. We discuss how cloud-based accounting systems can improve financial reporting, reduce costs, and enhance collaboration. However, we also examine the challenges associated with cloud computing, such as security concerns, data privacy, and compliance issues. Finally, we provide recommendations for organizations considering cloud-based financial accounting solutions. Cloud computing has emerged as a transformative force, revolutionizing the landscape for accounting firms. This comprehensive review delves into the profound impact of cloud computing on accounting firms, focusing on key dimensions such as efficiency, scalability, and data security. Examining the shift from traditional infrastructure to cloud based solutions, the review navigates through the tangible benefits and potential challenges that cloud adoption brings to the accounting domain. Efficiency stands out as a cornerstone of cloud computing’s influence on accounting firms. The agility and accessibility offered by cloud-based platforms streamline routine tasks, facilitating seamless collaboration among accounting professionals. The scalability afforded by cloud services empowers firms to dynamically adjust their computing resources, adapting to fluctuations in workload and business demands. This ensures that accounting firms can efficiently handle diverse workloads without being constrained by rigid infrastructure limitations. Scalability further intersects with efficiency, enabling accounting firms to optimize resource allocation and enhance overall productivity. The scalability of cloud solutions aligns with the dynamic nature of the accounting profession, allowing firms to scale up during peak seasons and scale down during lulls, ultimately fostering cost-effectiveness and operational agility. However, the review also critically evaluates the nuances of data security in the cloud computing paradigm. Addressing concerns related to data privacy, confidentiality, and compliance, the review navigates the intricate landscape of securing financial data in a cloud-based environment. It probes into the robustness of encryption protocols, authentication mechanisms, and compliance frameworks, ensuring a comprehensive understanding of the security implications inherent in cloud adoption by accounting firms. In conclusion, this review encapsulates the multifaceted impact of cloud computing on accounting firms. Efficiency gains and scalability advantages are juxtaposed against the imperative of fortifying data security. This examination provides a roadmap for accounting professionals, offering insights into harnessing the full potential of cloud technologies while ensuring the integrity and security of sensitive financial data. As accounting firms increasingly pivot towards cloud adoption, this review serves as a strategic guide, equipping practitioners with the knowledge to navigate the evolving landscape of cloud computing in the realm of accounting.